BOLON HOUSE ORNAMENTS AS A MEDIUM OF CHARACTER EDUCATION FOR THE SIMALUNGUN TRIBE COMMUNITY - Saragih, Alkausar (JURNAL PENDIDIKAN IPS, 2025)
This study aims to find out in depth the ornaments of the Bolon house building as a medium for character education in the life of the Simalungun indigenous people in North Sumatra. This study uses a qualitative descriptive method about the results of the presentation of data obtained through observation, interviews, literature review, documents. The results of data analysis show that the ornament of the Bolon house which is a house of pride and as a historic house for the Simalungun tribe is a means of character education media among the Simalungun people, this can be seen from several examples of ornaments found such as bohi-bohi ornaments, bodat marsihutuan, boraspati , ganjo mardompak, pinar appul-appul, porkis marodor, pinar andur-dur, pinar pahu-pahu patundal, pinar simarlipan-centipede, pinar bunga hambili, pinar ipon-ipon, pinar tali simuor-uor, pinar sulihni rotak, pinar horis hotala . The results of this study indicate that the ornament of the Bolon house is allegedly a character education such as the symbol of the Simalungun tribe's hospitality, helping to achieve goals, being able to adapt to the social environment wherever they are, having meaning as a symbol of order, and thoroughness, cleanliness, beauty, kindness and majesty, as the nature of mutual cooperation, a symbol of loyalty to keep promises.